Designing a Windows-Based Learning Application About the History of Batik in Indonesia - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Adwiyah, Rabiatul; Tarigan, Ray Rivandi; Gorat, Loveyanni Marito Benedikta (CV. Rayyan Dwi Bharata, 2024)
The development of information technology has brought significant changes to the world of education, including in history learning methods. Application-based learning provides a more interactive and effective learning experience. Traditional batik, which has developed over the past centuries, has produced various types and patterns of traditional batik that are unique to every region in Indonesia. Indonesian batik is very popular in various countries. Batik as a cultural heritage from our ancestors needs to be preserved so that it does not become extinct over time. This research aims to create a learning application to introduce batik originating from Indonesia. The application was built using Windows Visual Studio, making it easier for users to run the application and understand the information.